The first record and the description of a new species of Dendrolycosa Doleschall, 1859 (Araneae: Pisauridae: Pisaurinae) from Madagascar - Da Silva, Estevam L. Cruz; Griswold, Charles E. (Zootaxa, 2013)
Spiders, like other Madagascan organisms, exhibit remarkable richness and endemism (Griswold 2003). Whereas there are only just over 550 species known from Madagascar (Platnick 2013), the rate of new species discovery suggests that the total may be much higher. In a comprehensive study of the Madagascar spider fauna, Griswold (2003) found that 29% of the 207 genera and 85% of the 459 described species or subspecies known at that time are endemic to Madagascar. Notably, the spider fauna is not disharmonic and contains most of the families found in Africa or Asia. The spider fauna known to Griswold (2003) showed a relatively strong affinity to Africa (19 species and 22 genera shared exclusively by Africa and Madagascar), and much weaker affinity to Asia and the Indo-Pacific.